2019
DOI: 10.1177/2059513118822954
|View full text |Cite
|
Sign up to set email alerts
|

The development of a self-help intervention to build social confidence in people living with visible skin conditions or scars: a think-aloud study

Abstract: Introduction:People with a visible difference, such as scarring or a skin condition, can experience anxiety and intrusive reactions from others when in social situations. The use of products to conceal marks on the skin is provided in a number of different hospital services and by charities. However, there are relatively few psychosocial interventions available for these individuals.Objectives:To examine the views of skin camouflage users and practitioners on the acceptability, usability and need for a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In the UK, treatment guidelines recommend the use of CBT for anxiety and panic disorder in the general population, delivered within a stepped care model -first providing CBT selfmanagement interventions [9]. There is growing evidence suggesting self-help interventions offer an accessible and effective form of treatment, including condition-specific interventions, which have the benefit of addressing specific challenges within clinical groups [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, treatment guidelines recommend the use of CBT for anxiety and panic disorder in the general population, delivered within a stepped care model -first providing CBT selfmanagement interventions [9]. There is growing evidence suggesting self-help interventions offer an accessible and effective form of treatment, including condition-specific interventions, which have the benefit of addressing specific challenges within clinical groups [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although specialised psychosocial support for adolescents with a visible difference is eclectic and includes a variety of therapeutic approaches (Harcourt et al, 2018), previous research has shown that interventions combining techniques from SST and CBT can be effective in treating appearance-related distress . A lingering issue, however, has been the limited evidence of effectiveness to fully support the use of available interventions based on these techniques into practice Shah et al, 2014;Pasterfield et al, 2019; and for those with experiences of social anxiety Shah et al, 2014; and general appearancerelated distress (Muftin & Thompson, 2013).…”
Section: The Role Of Web-based Self-help In Treating Appearance-relat...mentioning
confidence: 99%
“…The basic principle of operation of fractional lasers is fractional photothermolysis developed by Man-stwierdzono obniżoną jakość życia wynikającą z poczucia wstydu, lęku i braku akceptacji społeczeństwa, co jest istotnym źródłem stresu [15,16]. Negatywny wpływ na sferę psychologiczną i emocjonalną może się wiązać z obniżeniem samooceny, unikaniem kontaktów towarzyskich, niechęcią do podejmowania pracy zawodowej, a nawet podwyższonym ryzykiem samobójstwa [17].…”
Section: Fractional Photothermolysis In Scar Treatmentunclassified
“…Goodman i Baron zaproponowali ocenę ilościową i jakościową opartą na typie i liczbie blizn [13] fect. People with visible scarring have been shown to have a reduced quality of life due to a sense of shame, anxiety, and the lack of public acceptance, which is an important source of stress [15,16]. In addition, the negative impact of scars on the psychological and emotional well-being of patients may be associated with reduced self-esteem, avoidance of social contacts, reluctance to take up professional work, and even an elevated risk of suicide [17].…”
mentioning
confidence: 99%